(untitled) (Bangladesh Journal of Anatomy, 2011)
Objective: Clinically the adverse effects of the diabetes on the out come of pregnancy are well established. The present study was designed to look for the impacts of gestational diabetes on the gross and histomorphological features of the umbilical cord. Type of study: A descriptive study having analytical components. Place and period of study: Department of Anatomy, Chittagong Medical College, Chittagong, from May 2006 to April 2007. Materials: Total fifty (50) umbilical cords with the placenta were collected within 36th to 40th weeks of gestation from Chittagong Medical College hospital and Memon maternity hospital of Chittagong City Corporation. Out of them 25 cords were from non diabetic pregnant mother (Control group) and 25 cords from mothers with gestational diabetes mellitus (GDM group). Method: After proper fixation with 10% formalin the diameter of the umbilical cord were measured with a vernier calipers in millimeters. Circumference, Cross-Sectional Area (CSA) of the umbilical cord and CSA of the Wharton’s jelly were measured by computerized micrometric method in millimeters and sq. millimeters respectively. Number of the umbilical vessels were examined and counted on the cut surface of the umbilical cord, later confirmed by histological examination. Presence or absence of the true knots were noted. Result: Among the gross morphological variables of the umbilical cord, the mean diameter was significantly larger in the GDM group than in the Control group (P< 0.05). Though the mean circumference, mean CSA of the umbilical cord and mean CSA of the Wharton’s jelly were found to be higher in the GDM group than in the Control group, but the difference did not reach to the significant level. All the cords of the GDM group, the umbilical cord contained two arteries and one vein, whereas, two cords of the Control group, the umbilical cord had three arteries and one vein and one cord contain four arteries and one vein. No true knots were found in any groups. Pearson’s correlation test revealed significant positive correlation in both GDM and Control groups between mean diameter and circumference of the umbilical cord (r = 0.881, P = 0.000 & r = 0.689, P = 0.000) and between CSA of the umbilical cord and Wharton’s jelly (r = 0.988, P = 0.000 & r = 0.990, P = 0.000). Key words: Umbilical cord; Gross and Histomorphology; GDM. DOI: http://dx.doi.org/ 10.3329/bja.v9i1.8143 Bangladesh Journal of Anatomy January 2011, Vol. 9 No. 1 pp 21-25